KOMBINASI TERMOTERAPI DAN KHEMOTERAPI DENGAN KULTUR APEKS DAN MERISTEM UNTUK ELIMINASI VIRUS MOSAIK PADA TEBU / The Combined Treatment of Thermotherapy and Chemotherapy with Apex and Meristem Culture for Mosaic Virus Elimination in Sugarcane - Ika Roostika; SEDYO HARTONO; DARDA EFENDI (Jurnal Penelitian Tanaman Industri, 2016)
There are several ways to eliminate virus, suach as the application of thermoterapi and chemotherapy technique, and also the apex and meristem culture. One way to control this disease is the use of virus-free seedlings. The objective of this study was to find out the effect of combined treatment between thermotherapy or chemotherapy with apex or meristem culture to mosaic virus elimination of sugarcane. There were four steps in this research: (1) Virus detection of mother plant, (2) Application of thermotherapy at 50oC and chemotherapy by using Ribavirin 25 µg/l combined with apex culture, (3) Application of thermotherapy and chemotherapy combined with meristem culture, and (4) Evaluation of virus elimination. The plant materials used were PS862 from Cirebon (PS862-Crb), PS881 from Surabaya (PS881-Sby) and PSJK922 (PSJK922-Bgr) from Bogor. Virus detection was conducted by TEM and RT-PCR analysis. The temperature for thermotherapy was 500C and the antiviral agent was Ribavirin (0 and 25 μg/l). The result showed that thermotherapy or chemotherapy combined with apex culture could not eliminate virus infection. The combined treatment of chemotherapy and meristem culture could eliminate SCSMV in variety PS862-Crb based on RT-PCR assay, however TEM analysis still detected the viral particle. It was suggessted to udertake virus indexing of large number of samples to see the rate of virus elimination.Keywords: Saccharum officinarum L., Ribavirin, Potyvirus, TEM, RT- PCR